Strengthening community participation in waste management through education and innovation - Joleha Joleha; Anggi Aprillia Cintami; Ashita Nadira Syamsudin; Fathurrahman Azizi; Harum Cantika Septiani; Khairatun Nisa; Nadia Hurul Aini; Putri Nilda Sari Lubis; R. Dea Julita; Satria Gandha Pratama; Totok Hadi Cahyono Pratama (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2024)
Urban waste management in Indonesia faces challenges from rapid population growth, increased waste generation, limited landfill capacity, and low public awareness of waste segregation. Although regulations promote the 3R principles (Reduce, Reuse, Recycle), their implementation is hampered by inadequate infrastructure and community participation. Bank Sampah IKHLAS exemplifies community-based waste management by empowering residents, especially women, to transform waste into valuable products while fostering environmental awareness. To enhance its effectiveness, the community service programs focused on education and motivation through socialization and personalized approaches to raise awareness of reducing waste volume at landfills. Creativity training based on the 3R principle was conducted, resulting in products like wallets, bags, laptop cases, and tumbler covers. The program increased awareness and participation, reflected in a rise in customers from 24 percent to 37 percent of total households. Although the increase is modest, the program successfully encouraged broader community involvement. Waste management has expanded from basic sorting to producing reusable items through recycling, showcasing the potential of integrated community-based approaches. This initiative highlights the role of education and creativity in building sustainable waste management systems.